Dynamics and control of flexible articulated space manipulators with large payloads - Wiedemann, Simon M. (Cranfield University, 2002)
This thesis studies the dynamics and control of flexible articulated space manipulators with large payloads similar to the Space Shuttle Remote Manipulator System. For dynamic response analyses an exact analytical method to compute natural frequencies and mode shapes of space manipulator systems with varying degrees of complexity is developed. Dynamic response analyses are performed comparing the results obtained using the exact mode shapes with those obtained when using assumed mode shapes for a series of different manipulator slew manoeuvres and Shuttle thruster firings. Possible methods for active vibration damping control of the manipulator are discussed, including the methods presented by other researchers. In this thesis it is proposed to use reaction wheels in a closed-loop control scheme, and its advantages and disadvantages compared to other methods are discussed. The problem of payload capturing and post-capture dynamics are addressed, as well as the dynamics following an emergency braking of the robot. For these cases, a simple method to estimate upper limits of dynamic responses is developed, and results obtained with this method for various example cases are compared with results computed by professional software. Finally the dynamic responses of a space station to various robot manoeuvres are analysed. These responses can have detrimental effects on micro-gravity and similar experiments. The analyses are performed using a simplified model of the International Space Station and its Mobile Remote Manipulator System.